The Golf Movement Screen Is Related to Spine Control and X-Factor of the Golf Swing in Low Handicap Golfers. Issue 1 (January 2021) - Gould, Zachariah I.; Oliver, Jon L.; Lloyd, Rhodri S.; Neil, Rich; Bull, Mark
Abstract : Abstract: Gould, ZI, Oliver, JL, Lloyd, RS, Neil, R, and Bull, M. The golf movement screen is related to spine control and x-factor of the golf swing in low handicap golfers. J Strength Cond Res 35(1): 240–246, 2021—The aim of the study was to investigate the association between the golf movement screen (GMS), x-factor, which is the separation between the upper torso and pelvis rotation, and biomechanical movements of the pelvis, thorax, and spine during the backswing and impact of a golf shot in low handicap golfers. In total, 62 golfers were involved in this study ( n = 40 male, n = 22 female); the mean age of the sample was 15.4 ± 2.4 years. For the GMS, all subjects were assessed on their movement ability over a total of 10 different exercises. After a thorough warm-up routine of practice swings, each golfer then performed a single trial for biomechanical analysis. Biomechanical data were collected using an electromagnetic tracking system. Four of the 10 exercises had a significant correlation with x-factor ( r = 0.25–0.33; p < 0.05). Four exercises had moderate correlations with spine rotation at the top of backswing. Spine side bend had a significant correlation with 9 of the 10 exercises and total GMS score ( r = 0.26–0.53, p < 0.05). Movements of the pelvis and thorax at the top of backswing had minimal associations with the GMS. At impact, trunk inclination, thoracic rotation, and squat had small to moderate significant relationships with biomechanical movements ( p < 0.05). Movement competency, as measured by the GMS, is associated with important aspects of swing mechanics. In particular, golfers who achieve better scores in the GMS have better spine control and can create a greater x-factor during the golf swing. Abstract : Supplemental Digital Content is Available in the Text.